2013
DOI: 10.4049/jimmunol.1301000
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis of Human NK Cells Is Not IL-15 Dependent

Abstract: IL-15 is a proinflammatory cytokine that plays an important role in the development and activation of NK cells and is a potential target for inflammatory disease therapy. Studies conducted in IL-15- and IL-15R knockout mice identified IL-15 as an important cytokine for NK cell homeostasis. Consistent with this information derived from genetically modified mice, we demonstrated that neutralizing IL-15 with a mouse anti-mouse IL-15 mAb (M96) depletes C57BL/6 mouse NK cells. An mAb directed against macaque IL-15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 26 publications
2
33
0
2
Order By: Relevance
“…To investigate whether steady-state exposure to IL-15 maintained the synthesis of selectin ligands on memory CD8 + T cells, we utilized an IL-15 neutralizing antibody (27). Indeed, neutralizing IL-15 caused circulating memory CD8 + T cells to reduce binding to E- and P-selectin, but did not affect the circulating frequency (Fig 2G–I).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether steady-state exposure to IL-15 maintained the synthesis of selectin ligands on memory CD8 + T cells, we utilized an IL-15 neutralizing antibody (27). Indeed, neutralizing IL-15 caused circulating memory CD8 + T cells to reduce binding to E- and P-selectin, but did not affect the circulating frequency (Fig 2G–I).…”
Section: Resultsmentioning
confidence: 99%
“…This mAb was based on the mouse, anti-human IL-15 mAb clone, M111, which is cross-reactive with RM IL-15 (66). Rhesusization was accomplished by exchanging the mouse amino acid sequences in the constant regions and variable binding surfaces for rhesus amino acid sequences, leaving variable region sequences responsible for IL-15 recognition unchanged (67, 68).…”
Section: Resultsmentioning
confidence: 99%
“…Because the IL-4Rα KO mouse was nonresponsive to both IL-4 and -13, we also investigated the role of IL-13 for NK cells and found that overexpression of IL-13 did not induce IL4-NK cells (Fig. S4) (19)(20)(21). Therefore, we examined macrophages in the liver and found that macrophages were remarkably increased in the mice overexpressing IL-4 compared with control mice by immunohistochemical staining (Fig.…”
Section: Resultsmentioning
confidence: 99%